Better Access to Justice by Public Recognition of Non-State Justice Systems? - Matthias Kötter (Max Planck Institute for European Legal History, 2015)
Access to justice is the term used to denote the institutional and social conditions for the realization of rights. In recent international security and development policy, the term is used in various ways as a guiding principle for "good law" and "good justice," and, for actors in these sectors, it has assumed central importance in their concepts and programs. Newer approaches particularly emphasize support for informal, non-state justice systems and their integration into the superordinate legal system, mainly in state law. Yet, does the official recognition of non-state legal systems guarantee access to justice, and under what conditions is this the case? Starting from this question the paper first retraces the formulation of the concept of access to justice in constitutional legal thinking principally at the end of the 1970s, and second discusses whether non-state justice systems can provide access to justice in an equivalent manner and which conceptual and normative drawbacks arise.
Additional information: Zugl.: Preprint (Manuscript Version) von Kötter, Matthias (2016) : Better Access to Justice by Public Recognition of Non-State Justice Systems?, In: Collin, Peter (Ed.): Justice without the State within the State. Judicial Self-Regulation in the Past and Present, ISBN 978-3-465-04268-6, Vittorio Klostermann, Frankfurt am Main, pp. 283-307
Keywords: 300; access to justice; rule of law; development policy; sociology of law; customary law